EMPLOYEE SELECTION PROCEDURES FOR HIGHER EDUCATION TEACHERS IN THE CONDITIONS OF UNIVERSITY AUTONOMY: UKRAINIAN PRACTICIES - Skyba , Yurii (Educological discourse, 2021)
The article presents the results of a study of domestic practices for recruiting vacant teacher positions in the context of university autonomy. After studying the practice of implementing personnel policy by leading domestic universities (Taras Shevchenko National University of Kyiv, National Pedagogical Dragomanov University, National Aviation University and Sumy State University) 8 stages of employee selection procedures were specified. At different stages of the competitive selection in the studied universities, certain differences were revealed, namely, in the requirements for the scientific and pedagogical experience of applicants, the availability of publications in scientometric databases, the procedure for checking documents submitted for the competition, consideration of documents by the competition committee, the procedure for discussing candidates during a meeting of the structural unit. Based on a survey of teachers regarding the university’s independent establishment of requirements for applicants for positions, it was found that the implementation of this tool of personnel autonomy was unavailable since about half of the respondents expressed warnings about the transparency and openness of its implementation in domestic universities.